Stimulation of Fat Oxidation, but no Sustained Reduction of Hepatic Lipids by Prolonged Pharmacological Inhibition of Acetyl CoA Carboxylase - Glien, M.; Haschke, G.; Schroeter, K.; Pfenninger, A.; Zoller, G.; Keil, S.; Müller, M.; Herling, A. W.; Schmoll, D. (Hormone and Metabolic Research, 2011)
Acetyl CoA carboxylase isoforms 1 and 2 (ACC1/2) are key enzymes of fat metabolism and their inhibition has been postulated to be beneficial for the treatment of the metabolic syndrome by decreasing ectopic fat accumulation. In order to validate this approach pharmacologically, we characterized the chronic effect of the small molecule ACC1/2 inhibitor SAR210 in 2 rodent models of fatty liver. Chronic administration of SAR210 increased serum ketone levels in both diet-induced obese mice and female ZDF rats. The inhibitor neither reduced hepatic triglycerides nor influenced body weight in either diet-induced obese mice or female ZDF rats. Thus, chronic pharmacological inhibition of ACC1/2 stimulated fat oxidation, which was, however, not sufficient to reduce hepatic triglycerides.
Keywords: diabetes; fat metabolism; insulin; liver metabolism; metabolic syndrome